Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK) Terhadap Belanja Modal Kota Bukittinggi - Chairunnisa Chairunnisa; Rani Manik; M. Azurul Azwar; Puty Andiny; Safuridar Safuridar; Yani Rizal (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This study aims to analyze the effect of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on Capital Expenditure in Bukittinggi City. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) of Bukittinggi City, covering the observation period from 2013 to 2024. The research method employed is a quantitative approach using multiple linear regression analysis. Data processing was carried out using the EViews application to examine the relationship and influence of each independent variable on the dependent variable.The results of the study indicate that Local Own-Source Revenue has a positive and significant effect on Capital Expenditure in Bukittinggi City. In addition, the General Allocation Fund is also proven to have a positive and significant effect on Capital Expenditure. These findings suggest that the higher the PAD and DAU received by the local government, the greater the allocation of capital expenditure to support regional development. Furthermore, the Special Allocation Fund also shows a positive and significant effect on Capital Expenditure. This confirms that these three sources of regional revenue play an important role in increasing capital expenditure in Bukittinggi City.